Varianti del tipo del Sonderling nel romanzo della Wende: Ein weites Feld di Günter Grass (ENTHYMEMA, 2020)
Grass’ novel, published in 1995, has been the object of a lively discussion centered on the author’s opinions on the German Unification process. Among the controversial issues is the choice of a main character that presents himself as an alter-ego or a révenant of Theodor Fontane, and speaks by quoting his works and, above all, imitating his style (in particular his epistolary style, and, from his novels, the conversational tones). The point is that this choice can be viewed as involving a trivialization of the dramatic events that occurred after the fall of the Berlin wall.  Indeed, in the character and his idiolect, Grass reproduces a typical figure of the German literary tradition, the ‘Sonderling’, revisiting the harmless pedantic (traditional) character by giving him a slightly subversive role towards the rethoric of the Unification.